A systematic review on design thinking in science education research (DTiSER) on 21st century skills - Mukhammad Aji Fatkhurrohman; Ida Hamidah; Andi Suhandi; Achmad Samsudin (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Design thinking is essential for developing 21st-century competencies, and there is a growing need and interest in introducing design thinking to science education students.Aim: The purpose of this study was to review high-quality empirical research on design thinking in science education research (DTiSER) and explore future research perspectives.Method: A literature review based on a five-stage methodology comprising of (1) research article collection from the databases, (2) research article inclusion/exclusion norms, (3) reviewing the processed research articles, (4) analyzing the research articles to extract the information, and (5) inferring the extracted information to derive at the future research direction. The paper contributes to reviewing 31 research articles, specifically on design thinking in science education research (DTiSER).Results: The results indicate that: (1) Research trends on design thinking in science education research (DTiSER) between 2015 and 2023 increased. (2) The United States is a country that mainly conducts research on design thinking in science education research (DTiSER) between 2015 and 2023 (3) Research trends of highly cited papers published in academic journals between 2015 and 2023, i.e., articles written by Smith et al. (4)  The science materials that have been applied to design thinking from 2015 to 2023 are electricity, magnetism, mechanics, climate, planets, earth science,  conservation biology, environment, thermodynamics, disaster mitigation, soil classification,  microba and organisms.Conclusion: The implementation of design thinking in science education research refers to science materials applied in real-life contexts. Therefore, the implementation of design thinking can pave the way for broader innovations in contexts relevant to science content and also in science learning innovations.